Enzyme replacement therapy in orphan and ultra-orphan diseases - Moore, David F.; Ries, Markus; Forget, Evelyn L.; Schiffmann, Raphael (PharmacoEconomics, 2007)
BackgroundFabry-Anderson disease is an x-linked deficiency of lysosomal α-galactosidase A (GALA), resulting in chronic renal failure, cardiac arrhythmia, hypertrophy, valvular disease, pain (acro-paraesthesiae) and stroke, together with premature mortality. The disease has a significant impact on quality of life (QOL), as illustrated by studies using the EQ-5D. A specific treatment is available for Fabry-Anderson disease consisting of intravenous enzyme replacement therapy (ERT) of the deficient enzyme. The variable clinical efficacy and cost of ERT has resulted in reluctance by some health providers to approve it.MethodsWe use the limited QOL data available in the Fabry-Anderson disease literature on ERT to derive standard economic metrics. These were derived by bootstrap estimates of the incremental net benefit (INB) statistics together with a cost-effectiveness acceptability curve relating the willingness to pay to the probability that the INB was >0. The estimates were further developed by adoption of a supplementary Bayesian approach utilising a sceptical and enthusiastic prior of the INB of ERT in Fabry-Anderson disease.ResultsERT for Fabry-Anderson disease is not economically viable by standard health programme evaluation metrics. Based on current ERT costs (year 2005 values), derivation of the INB distribution, and a Bayesian analysis using an enthusiastic and sceptical prior of the INB, an upper ($US350 000 over 1 year) and lower ($US175 000 over 1 year) economic cost, respectively, of ERT was derived.ConclusionThe cost of ERT will always result in a net deficit to society under current costing and ERT efficacy as determined by the QALY metric. The rules of fair cooperation should govern decision making both for ERT in Fabry-Anderson disease and for funding therapeutic advances in other rare diseases belonging to the orphan and ultra-orphan categories.
First online: 22 September 2012
Gesehen am 15.05.2019